The effect on twinning rate of transferring double vitrified-warmed embryos in women of advanced reproductive age: a retrospective study - Yamei Xue; Kun Li; Songying Zhang (PeerJ, 2020)
Twin pregnancies are associated with greater risk of neonatal morbidity and mortality than a singleton. This study was performed to investigate the twin pregnancy rate when two vitrified-warmed embryos are transferred in women of advanced reproductive age (≥35 years at the time of oocyte retrieval) and to evaluate the implications of findings in selecting candidates for elective single embryo transfer (eSET). A retrospective analysis of data which included 2,038 women aged 35–45 years, who underwent vitrified-warmed double embryo transfer (DET), from January 2013 to December 2016 was undertaken. Pregnancy and twin rates were estimated after stratifying by prognostic profile. The twin pregnancy rate was lower in women with poor prognosis (12/96, 12.5%) as compared with that in women with favorable prognosis (102/374, 27.3%) and average prognosis (78/346, 22.5%) with significant differences (P < 0.05). The twin rate for women with favorable prognosis was 29.2% (70/240) in the cycles of women aged 35–37 years, 26.8% (26/97) in the cycles of women aged 38–40 years and 16.2% (6/37) in the cycles of women >40 years. The twin rate for women with average prognosis was 25.8% (51/198) in the cycles of women aged 35–37 years, 22.0% (22/100) in the cycles of women aged 38–40 years and 10.4% (5/48) in the cycles of women >40 years. The twin rate for women with poor prognosis was 15.3% (9/59) in the cycles of women aged 35–37 years, 10.3% (3/29) in the cycles of women aged 38–40 years and 0% (0/8) in the cycles of women >40 years. From these results, it was concluded that women with a favorable or average prognosis have a high risk of twin pregnancies. The finding can be used to guide future practice: that is, performing eSET in women with favorable or average prognosis and DET in women with poor prognosis.